Evaluation of the Impacts of Chemotherapeutics on Odontogenesis Process: Findings from a Systematic Review - Smith, Camila Valente; Silva, Grazyelle Sebrenski da; Silva, Felipe Rodolfo Pereira da; Barcellos, José Fernando Marques; Furtado, Silvânia da Conceição (Journal of Morphological Sciences, 2019)
This study aimed to examine and recognize the impacts of antinoplastic chemotherapeutics on the development of dental germ, employing a systematic review. A retrieving in the literature was carried out, using several medical and scientifical databases (ClinicalKey, Cochrane Library, Google Scholar, MedLine, PubMed, and ScienceDirect), by two investigators separately. In the end of this systematic search, eight articles met the required criteria for inclusion and, therefore, composed the results. Among these, four articles are about observational studies in humans, and the other four about experimental animal studies. In both cases and species, anomalies such as microdontia, hypodontia/agenesia, and root shortening were observed. The severity and frequency varied according to the nature of the chemotherapeutics applied as well as the administered dosage and the patient's age at the time of first exposure. Through the results, it was possible to show the direct impacts of chemotherapy on the odontogenesis process as well as factors such as the type of chemotherapy, the age of the individual at the time of first exposure and the dosage used. All of those should be taken into account when choosing a therapeutic protocol for an oncology patient. Besides, we observed the need for more studies in this area and that these should be standardized in order to allow an objective and direct analysis of comparable parameters, even when different approaches are used.
Keywords: dental anomaly; amelogenesis; chemotherapy; evidence-based dentistry; oral health